Fetal brain assessment: new tools - Lacunza Paredes, Rommel (2021)
The evaluation of the fetal brain is an essential point in obstetric ultrasound due to the large number of malformations that can be diagnosed. The ISUOG guide provides us with the elementary sections for the suspicion of brain pathology; but we can extend and improve our ultrasound with the visualization of easily reproducible structures, such as the anterior complex, corpus callosum, Sylvian fissure and the fourth ventricle. We present some tools to complement the evaluation of the fetal brain.